Analisis Pendapatan Petani Pala di Desa Rutah, Kecamatan Amahai, Kabupaten Maluku Tengah - Wijaya, Oki; Wattiheluw, Nurul Jihan Fitriyah; Triyono, Triyono (Universitas Galuh, 2024)
This research was conducted in Rutah Village, Amahai District, Central Maluku Regency. This research aims to determine the costs, revenues and income of nutmeg farming in Rutah Village, Amahai District, Central Maluku Regency. Sampling used the purposive sampling method with a sample of 30 farmers. The results of the research show that the average costs incurred for nutmeg farming in terms of seeds and flowers (mace) are IDR. 259,037 per planting season, the average cost incurred for processing candied nutmeg is Rp. 298,062, the average total income obtained by farmers is IDR. 3,811,000 per season, and the average income earned by farmers is IDR 3,186,837 per planting season.